Antioxidant and antimicrobial activity of drumstick (Moringa oleifera) leaves in herbal chicken sausages. Issue 2 (December 2015) - Jayawardana, Barana C.; Liyanage, Ruvini; Lalantha, Nirosh; Iddamalgoda, Supeshala; Weththasinghe, Pabodha
Abstract Drumstick (Moringa oleifera) leaves were evaluated for antioxidative capacity and antimicrobial activity when incorporated in chicken sausages. Different concentrations (0.25%, 0.5%, 0.75% and 1%) of M. oleifera leaves (MOL) incorporated sausages and two controls without MOL (one with added artificial antioxidant and other without any antioxidant) were prepared. TBARS value, pH, microbial analysis, sensory panel scores and instrumental color were assessed. Sausages with 0.5%, 0.75% and 1% MOL showed significantly lower (p < 0.05) TBARS value compared to 0.25% MOL and the two control samples. Sausages with 0.5%, 0.75% and 1% MOL showed significantly (p < 0.05) low pH values from the 2nd week to the 5th week of storage and significantly (p < 0.05) low Total Plate Count throughout the storage period, compared to 0.25% MOL and the two control samples. The sensory panel did not detect any difference in any sensory attribute in chicken sausages with 0.25% and 0.5% MOL compared to the controls. The study identifies the significant antioxidant and antimicrobial potential of Drumstick leaves in chicken sausages.